Encouraging Women Participation in Free and Open Source Software Organizations: The GNOME OPW Initiative - Martínez de la Cruz, Victoria (2013)
Even though the global demand for computing talent is surging, women’s representation in the computing profession has steadily declined. This phenomenon is not new and is present worldwide, not being associated with a particular country or culture. The reason of why women tend to avoid computing careers does not have a clear answer yet and is being researched by several organizations, institutions and companies. The GNOME Outreach Program for Women (OPW) internships has been inspired by this fact. Focused on the context of Free and Open Source Software (FOSS) organizations, the GNOME’s OPW is performing a great effort for the integration of women in this particular area of CS. This paper analyzes several issues on how can women be encouraged to participate in FOSS organizations, based on the experiences of a former GNOME OPW intern. In addition we discuss the role of different stakeholders (organizations, universities) in improving women participation in FOSS organizations in Argentina.